The performance of Portuguese banks under Basel III : how have the new capital requirements impacted the profitability of Portuguese banks? - Santos, Filipe Ferreira dos (2018)
This Dissertation analyzes how the new capital requirements imposed by Basel III framework affected the profitability of Portuguese banks, during and after the Global Financial Crisis (GFC). The present Dissertation employs the Multiple Regression analysis to study how Common Equity Tier 1, Tier 1 and Total Capital movements, could affect the Return on Equity and Return on Assets of Portuguese banks. This research collected some relevant empirical findings from the estimated regressions. This research’s findings suggest that there is a negative relationship between Common Equity Tier 1 and Return on Equity, and that Tier 1 and Total Capital contributes positively to the increase of profitability. Moreover, Common Equity Tier 1 presents coefficients with higher magnitude comparing with the other capital ratios, having a greater impact on Portuguese banks’ profitability. Finally, higher capital ratios affect the credit channel in the Portuguese banking sector and could impact the profitability of Portuguese banks.